Airy beam assisted NIR-II light-sheet microscopy. (December 2022) - Liu, Pengfei; Shi, Tianze; Li, Hongwei; Chen, Hongyu; Huang, You; Ma, Huizhen; Zhu, Tianyu; Zhao, Rong; Li, Yuan; Xin, Qi; Liu, Ling; Sun, Si; et al.
Abstract: Near-infrared II (1000–1700 nm) three-dimensional (3D) microscopy addresses a significant improvement on the penetration depth for bioimaging, but is challenging in high z -direction spatial resolution, leading to imaging distortion in deep tissue bioimaging. Here, we developed Airy beam-assisted NIR-II light-sheet Microscope (NIR-II Airy LSM) to improve z -direction spatial resolution with large field of view (FOV) on thick biological specimens via self-healing properties of the propagation-invariant field. The axial resolution was measured to be consistently 3.5 µm across the whole FOV (∼ 600 µm), about 4 times higher than traditional Gaussian-beam based microscopy (∼ 15 µm). Besides, the NIR-II Airy LSM demonstrates 2–3 times higher signal background ratio (SBR) than NIR-I imaging, at the penetration depth of approximately 2.5 mm. The increased spatial resolution and SBR allows us to observe pathological conditions and progression of glomeruli and tubules of radiation induced kidney injury and discriminated integral damage degree of intestinal mucosal cells from intestinal tissue accurately via 3D volumetric multiplexed imaging. The improved NIR-II light-sheet microscopy exhibit complete 3D imaging capabilities of whole bio tissues without sacrificing axial resolution and avoid imaging distortion under deep tissue. Graphical Abstract: We have developed an advanced 3D imaging modality, the NIR-II Airy LSM, with deep tissue penetration, less laser irradiation and balanced spatial resolution on a large FOV. The theoretical analysis and 3D volumetric imaging on microspheres and biospecimen show the improvement axial resolution up to 4-times higher than the traditional Gaussian beam-based LSM with an extended usable FOV over 600 µm as shown in (A-C). Further, the efficient NIR-II fluorophore, gold clusters, allows penetration of tissues over 2.5 mm and 2-times higher SBR than NIR-I imaging as shown in (D-G). The superior imaging performance allows us to observe pathological conditions and progression of radiation-induced intestinal injury and distinguish integral damage degree from accurate 3D volumetric multiplexed imaging. Overall, this is a powerful, easy-to-implement approach that needs only a SLM or a phase mask to modulate the cubic phase on the pupil. Integrating with a fast-developing range of highly bright fluorescent or luminescent probes emitting within the NIR-II window, making it to be an optimized choice for noninvasive intravital imaging method for resolving cellular structures in vivo and ex vivo . ga1 Highlights: NIR-II ALSM demonstrates high axial resolution (3.5 µm) over long FOV (~600 µm) on thick specimens. The NIR-II Airy LSM demonstrates 2-times higher SBR than NIR-I imaging, at the penetration depth of ~2.5 mm. The radiation induced damage degree of intestinal mucosal cells can be discriminated accurately via 3D volumetric imaging.